Effect of S100A6 over‐expression on β‐catenin in endometriosis. Issue 9 (4th June 2015) - Liu, Zequn; Zhang, Xiaoling; Chen, Meihong; Cao, Qing; Huang, Donghua
Abstract Aim S100A6 is over‐expressed in several human tumors, including pancreatic carcinoma, malignant fibrous histiocytoma, breast, colon, and gastric carcinoma, but little is known about the role of S100A6 in endometriosis. The aim of the present study was to investigate the effect of S100A6 over‐expression on β‐catenin in endometrial stromal cells. Methods Endometrial stromal cells were transfected with an hS100A6‐expressing recombinant lentivirus construct. The expression of β‐catenin was assessed using western blot and reverse transcription‐polymerase chain reaction. Results S100A6 over‐expression promoted β‐catenin expression at the RNA and protein levels, in endometrial stromal cells. Conclusions S100A6 induces expression of β‐catenin in endometrial stromal cells.